Pharmacogenetic Study of Anti‐TB Drugs in the Native Ancestry Peruvian Population - Luis Jaramillo‐Valverde; Mary K. Horton; Julio A. Poterico; Cristina M. Lanata; Heinner Guio (Pharmacology Research & Perspectives)
ABSTRACT In Peru, 33 113 individuals were diagnosed with tuberculosis (TB) in 2023. While TB treatments are generally effective, 3.4% to 13% of cases are associated with significant adverse drug reactions, with drug‐induced liver injury (DILI) being the most prevalent. Limited data exist on genetic risk factors for DILI in Latin America; even less is known about these factors in native Peruvian populations. This study aimed to determine the prevalence of TB drug‐metabolizing genotypes in these populations. A cross‐sectional analysis was conducted using genetic data from 254 participants from the Peruvian Genome Project (PGP) representing three subpopulations: Coast, Andes, and Amazon. Twenty‐three genes associated with TB treatment, include isoniazid, rifampin, ethambutol, and pyrazinamide, as identified in the PharmGKB database, were analyzed. Significant differences were observed in genotype frequencies among subpopulations for AGBL4, NAT2, GSTP1, SLCO1B1, NOS, and CYP2B6 genes. The Amazonian population demonstrated a higher risk of DILI due to the increased prevalence of hepatotoxic alleles in AGBL4, GSTP1, and SLCO1B1. In contrast, alleles in the NOS gene indicated a lower risk of hepatotoxicity in the Andean population. However, the high‐risk genotypes identified in the study's native Peruvian populations exhibit distinct prevalence patterns compared to those reported in the 1000 Genomes Project. These findings can inform the development of personalized therapeutic strategies to improve TB treatment outcomes among Peru's diverse subpopulations.